1987
DOI: 10.4319/lo.1987.32.1.0112
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transport of heavy metals by settling particles in Lake Zurich

Abstract: Transport into sediments of the trace elements Cu, Zn, Pb, Cd, Cr, and Sr by settling particles was investigated in Lake Zurich; the concentrations of these elements in settling particles collected in sediment traps and in the water column were determined at different times of year. Correlations of trace element concentrations with the various main components of the settling particles (biological material, calcium carbonate, manganese and iron oxides, silicate minerals) and examination of seasonal variations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 18 publications
3
91
0
1
Order By: Relevance
“…2. Ca was determined by flame atomic absorption of acid--digested samples; CO, was evaluated by infrared absorption; organic carbon was measured by high temperature combustion after removal of inorganic C (Sigg et al 1987). Some sedimentation patterns are similar in each lake.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…2. Ca was determined by flame atomic absorption of acid--digested samples; CO, was evaluated by infrared absorption; organic carbon was measured by high temperature combustion after removal of inorganic C (Sigg et al 1987). Some sedimentation patterns are similar in each lake.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Baines and Pace (1994) recently demonstrated that the sinking flux of C, N, and P was correlated with metalimnetic algal pigment concentrations along a trophic gradient. Similarly, Sigg et al (1987) determined that fluxes of organic matter increased during periods of high productivity. Al: though these studies demonstrate that the settling fluxes of organic matter are related to the biomass of planktonic matter in the water column, they make no distinction between the sedimentation of dead organisms (particulate organic carbon) and the settling fluxes of aquagenic organic matter coagulated with inorganic colloids.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…These elements can easily move from the solid to liquid phase of water and vice versa following changes in both the biotic and abiotic components. The metals in the sediments may re-solubilize in different chemical forms due to changes in environmental conditions such as pH, redox potential (Eh), dissolved oxygen and presence of organic carbon [13][14][15][16] . The analysis of heavy metals in sediments allows us to detect contamination and also provides information on the critical areas of aquatic systems 1,7,9,17,19,20 .…”
Section: Introductionmentioning
confidence: 99%